Liesbeth François. Andares vacilantes. La caminata en la obra de Sergio Chejfec. Rosario: Beatriz Viterbo Editora, Ensayos Críticos, 2018. - Berg, Edgardo (Badebec, 2019)
Liesbeth François. Andares vacilantes. La caminata en la obra de Sergio Chejfec. Rosario: Beatriz Viterbo Editora, Ensayos Críticos, 2018.